When High Tech ceases to be High Growth: The Loss of Dynamism of the Cambridgeshire Regio - Erik Stam; R. Martin (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2012)
This paper analyses mechanisms of decline and renewal in high-tech regions, illustrated with empirical evidence on the Cambridgeshire high-tech region in the UK. The paper contributes to ecological ('carrying capacity') and evolutionary (path dependence) theories of regional development. It provides a longitudinal, multilevel analysis of invention, firm, and industry dynamics and change in the supply and costs of resources in order to explain the decline of high-tech regions. While expansion of the Cambridgeshire high-tech region has been sustained over time, recently forces of decline have been stronger than those of renewal. Decline in employment has been most marked in the local telecommunications and biotech sectors, while the creation of variety by new firms has fallen off most strongly in the local IT software & services industry. Increasing diseconomies of agglomeration are in evidence, together with a contraction of finance that may have been a harbinger of financial stringency to come.
Keywords: 330; high-tech regions; industrial dynamics; innovation; entrepreneurship; cluster decline